Q. 54.7( 13 Votes )

If a function f:

Answer :

Given


We need to find f(1), f(–1), f(0) and f(2).


When x > 0, f(x) = 4x + 1


Substituting x = 1 in the above equation, we get


f(1) = 4(1) + 1


f(1) = 4 + 1


f(1) = 5


When x < 0, f(x) = 3x – 2


Substituting x = –1 in the above equation, we get


f(–1) = 3(–1) – 2


f(–1) = –3 – 2


f(–1) = –5


When x = 0, f(x) = 1


f(0) = 1


When x > 0, f(x) = 4x + 1


Substituting x = 2 in the above equation, we get


f(2) = 4(2) + 1


f(2) = 8 + 1


f(2) = 9


Thus, f(1) = 5, f(–1) = –5, f(0) = 1 and f(2) = 9.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Let A = {–1, 0, 1RS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

Let <span lang="EMathematics - Exemplar

Let <span lang="EMathematics - Exemplar

Express the functRD Sharma - Mathematics

Let <span lang="EMathematics - Exemplar

. Let f:(2,RS Aggarwal - Mathematics

. Let f: R RS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

Find the values oMathematics - Exemplar